Industry 4.0 technologies adopted by logistics companies for sustainability and competitiveness - Lyu, Zhan; Aktas, Emel; Liang, Jing (Elsevier, 2026)
Due to the emergence of Industry 4.0 and 5.0, numerous emerging technologies such as artificial intelligence (AI), the Internet of Things (IoT), digital twins, blockchain, and autonomous vehicles are increasingly impacting various aspects of the global logistics industry, which is undergoing significant transformation. These technologies can potentially enhance operational efficiency, reduce costs, improve customer satisfaction, and foster a more responsive and sustainable logistics environment. However, their adoption presents considerable challenges, particularly for third-party logistics (3PL) companies in highly competitive markets like the United Kingdom and China. These challenges include high implementation costs, data security risks, regulatory compliance issues, and the need for the workforce to adapt to new technological environments. This study provides a comparative analysis of the application and impact of these technologies on 3PL companies in the United Kingdom and China. Drawing on insights from logistics experts using the best–worst method, the research identifies best practices and offers strategic recommendations for optimizing technology integration within different market contexts. The research findings indicate that digital twins have the greatest impact on 3PL companies. Additionally, the study explores the varying degrees of influence that different technologies exert on various areas within 3PL companies. This study contributes to a deeper understanding of how emerging technologies can be effectively integrated into the operations of 3PL companies to enhance competitiveness and operational efficiency while also considering regional differences in market conditions, regulatory environments, and technological implementation, paving the way for further in-depth research.
Keywords: 46 Information and Computing Sciences; 35 Commerce, Management, Tourism and Services; 3506 Marketing; Machine Learning and Artificial Intelligence; 9 Industry, Innovation and Infrastructure; Operations Management; Information Systems; Technology Management; Operations Research; Sustainable Development; Technological Change; Industrial Organization